Pengaruh Produktivitas Tenaga Kerja Dan Pengelolaan Persediaan Bahan Baku Terhadap Kinerja Operasional Perusahaan : (Survei Pada Industri Kecil Sepatu Dan Sandal Di Kecamatan Mangkubumi) - Melda Acassa Sopyani (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
The purpose of this study was to determine the effect of labor productivity and raw material inventory control on the Company's Operational Performance (Survey on small shoes and sandals industry in Mangkubumi District). The method used in this study is a quantitative method, with a research sample of 64 respondents who are the owner, the person in charge of production, the person in charge of raw materials and the quality control team. The analytical tool used in this research is multiple linear regression. The results showed that simultaneously Labor Productivity and Raw Material Inventory Management had a significant effect on the Company's Operational Performance. Partially, Labor Productivity has a positive and significant effect on the Company's Operational Performance. Partially Raw Material Inventory Management has a positive and significant effect on the Company's Operational Performance.